Effects of regional trade agreements using a static and dynamic gravity equation - Inmaculada Martínez-Zarzoso; Felicitas Nowak-Lehmann D.; Nicholas Horsewood (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2006)
This paper evaluates the static effects of preferential agreements between several economic blocs and areas using a dynamic gravity equation. The main aim is to investigate whether regionalism has fostered intra or/and extra blocs international trade, taking into account the existence of heterogeneity over time and across countries and testing whether a dynamic model is preferred to the traditional static specification of the gravity model. This paper argues that the gravity model should be best estimated using Blundell and Bond's (1998) system-GMM estimator. This procedure remedies some econometric problems such as regressor endogeneity, measurement error and weak instruments, and controls for timeinvariant country-specific effects such as distance or common language.
Keywords: F14; F15; 330